IMPLEMENTASI STRATEGI DEMONSTRASI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 2 SINJAI TIMUR KABUPATEN SINJAI - Husain, Halimah; Wardana, Wardana (JURNAL AL-QAYYIMAH, 2021)
This paper discusses the implementation of demonstration strategies in learning Islamic education in junior high schools. Aims to reveal about the implementation of the demonstration strategy in Islamic Religious Education learning and its contribution at SMP Negeri 2 Sinjai Timur, Sinjai Regency. This research is included in the type of field research with a qualitative method approach. The data were obtained using several instruments, namely; observation guide, interview guide, and documentation tool. The results showed that the demonstration method is a method that uses demonstrations to clarify an understanding or to show how to do something to students. The implementation of learning, especially Islamic Religious Education at SMP Negeri 2 Sinjai Timur, Sinjai Regency, first of all in a theoretical way, meaning that in presenting lessons only with oral explanations, even though verbally it is not focused on the lecture method but still interspersed with movements (demonstrating) delivered by the teacher. The contribution can be seen in 3 dimensions, namely, Guiding the practice of students' Islamic teachings, increasing student achievement and making students enthusiastic about learning because students can practice directly in front of the class.